Rothe method for a mixed problem with an integral condition for the two-dimensional diffusion equation - Nabil Merazga; Abdelfatah Bouziani (Abstract and Applied Analysis)
This paper deals with an initial boundary value problem with an integral condition for the two-dimensional diffusion equation. Thanks to an appropriate transformation, the study of the given problem is reduced to that of a one-dimensional problem. Existence, uniqueness, and continuous dependence upon data of a weak solution of this latter are proved by means of the Rothe method. Besides, convergence and an error estimate for a semidiscrete approximation are obtained.